The Role of Digital Innovations in the Transition of English Literature - Sanganand Bagde (Emerging Trends in Languages, 2026)
The context of English literature has changed significantly with modernization of the digital age that is creating massive impacts on the creation, dissemination, and interpretation of literature. The rapid evolution of digital technologies has profoundly influenced the study, creation, and distribution of English literature in the contemporary period. When one considers the relationship between literature and digital innovation, one may summarize these disruptive forces as both a challenge to and opportunity for literature hybridization of past forms. This paper examines the influence of digital innovations on the transformation of literary practices, especially in a transition from conventional print culture to digital platforms. It explores how digital technologies have transformed reading practices, textual analysis, and the work of criticism, while highlighting the nascent field of digital humanities. The study also discusses how multimodal texts, participatory narratives, and digital storytelling challenge conventional literary structures and encourage new forms of participation and creation. Digital innovation, making literary spaces more accessible and democratic, is, on the other hand, also a process that dilutes creativity, genuineness, and does something to the role of academic literary studiers. The paper discusses how digital transformation constitutes not only a technological transition but also a cultural and epistemological shift that redefines the parameters and future of English literary studies. By analyzing significant technological advancements and their effects on modern literature, this study demonstrates the transformative potential of digital innovation in redefining English literature in the twenty-first century.
Keywords: artificial intelligence; digital innovation; information technology; interactive narratives; social media